RMB exchange rate regime reform and the Trilemma facing LOEs - Ming Feng; Hao Cheng (China Finance and Economic Review, 2016)
The discussions on Renminbi (RMB) exchange rate could not depart from the ongoing reform of RMB exchange rate regime, which must be designed and promoted as an integral part of the large open economy macroeconomic policy framework. As a large open economy facing the Trilemma, China should explicitly establish the principle of domestic monetary policy dominance in the impossible trinity, with the exchange rate policy and capital account management should both conform to this fundamental principle. Simplistically pegging RMB to the US dollar will result in lack of flexibility and violate this principle, especially against the backdrop of unsynchronized economic cycles of major economies and the prospect of further Fed tighten up that the real effective exchange rate of RMB moves passively along with the US dollar which cannot reflect the relative changes in economic fundamentals in China and abroad, which will cause distortions, resulting in resource misallocations and loss of welfare. The reform of RMB exchange rate regime should be market-oriented, towards a direction with more flexibility.
Keywords: 330; Impossible trinity; RMB exchange rate regime; Large open economy